The feasibility of high-resolution distributed acoustic sensing (HR-DAS) for measuring blast waves - Denny, Jack; Critchley, Richard; Lee, Timothy; Beresna, Martynas; Brambilla, Gilberto; Masoudi, Ali (Springer, 2026)
Experimental measurement of explosive blast wave overpressures is demanding, requiring specialist instrumentation that can survive extreme pressures (> 1 MPa) over short durations (< 5 ms), yet sensitive enough to resolve spatial and temporal features that vary in the mm and μs range, respectively. Distributed acoustic sensing (DAS) is an alternative approach that measures dynamic strain histories at multiple locations along a single optical fibre. This study investigates the capability of a high-resolution DAS (HR-DAS) system to capture strain responses induced by side-on (incident) blast overpressures, compared to a reference piezoelectric pressure sensor. While explosive events can produce overpressures exceeding 1 MPa, lower overpressure regimes (40–72 kPa) were adopted in this study for proof-of-concept demonstration of the HR-DAS methodology. Strain histories measured by the HR-DAS displayed reasonable qualitative agreement with overpressure histories measured using piezoelectric sensors, with the blast wave positive phase durations showing close quantitative agreement. Better correlation was observed between the measurements when HR-DAS sensors were mounted perpendicular to the blast wave propagation, validating the system’s efficacy under uniform loading conditions. However, discrepancies were observed for sensors aligned parallel to the wave direction, highlighting the limitations of the spatial resolution of the HR-DAS and fibre orientation when subjected to a dynamic, spatially varying loading scenario. Findings emphasise the importance of sensor placement and configuration for distributed pressure analysis. Proof of concept results and recommendations from this study highlight an interesting opportunity for developing a novel blast pressure metrology, enabling multiple measurement points from a single optical fibre, that is small, flexible, and relatively low cost, addressing several limitations with conventional pressure instrumentation methods.
Keywords: 40 Engineering; Bioengineering; Aerospace & Aeronautics; 4012 Fluid mechanics and thermal engineering